Isolation, Identification and Characterization of Process Related Impurity in 2-Isopropyl-4-hydroxy Anisole - THAPA, M.; VANSADIYA, R.; NAUTIYAL, R.; SHAH, C.C.; DEO, KESHAV (Asian Journal of Chemistry, 2010)
One impurity in 2-isopropyl-4-hydroxy anisole at level ca. 0.2 % at relative retention time ca. 2.30 is detected by reversed phase HPLC. This impurity is isolated from the enriched impurity sample using reversed phase preparative HPLC. Based on the spectral data (IR, NMR, 13C NMR and MS) impurity is characterized as dimer of 2-isopropyl-4-hydroxy anisole.